Adjunctive use of physostigmine salicylate (Anticholium®) in perioperative sepsis and septic shock: study protocol for a randomized, double-blind, placebo-controlled, monocentric trial (Anticholium® per Se) - Zimmermann, Johannes B.; Pinder, Nadine; Bruckner, Thomas; Lehmann, Monika; Motsch, Johann; Brenner, Thorsten; Hoppe-Tichy, Torsten; Swoboda, Stefanie; Weigand, Markus A.; Hofer, Stefan (Trials, 2017)
Severe sepsis and septic shock remain a major challenge, even in modern intensive care. In Germany, about 68,000 patients die annually because of septic diseases, characterized by a complex systemic inflammatory response. Causal treatment of the underlying infection is essential for successful management of sepsis, but the course can be positively influenced by supportive and adjuvant measures. The cholinergic anti-inflammatory pathway (CAP) represents a new approach to adjunctive therapy of septic diseases and can be pharmacologically activated by the acetylcholinesterase inhibitor physostigmine (Anticholium®). Promising effects can be found in several in vitro and in vivo models of sepsis, such as a reduction in pro-inflammatory cytokines and improved survival.